Market Access, Growth, and Poverty Reduction in a Kaldorian framework - Karshenas, Massoud; van der Geest, Willem (Journal of Income Distribution®, 2017)
The role of access to markets in industrialized countries for economic development and poverty reduction in low-income countries is investigated. The conditions under which economic growth and exports have a statistically robust effect on poverty reduction are demonstrated for a large number of low-income countries that suffer from mass poverty. Export growth is particularly important in providing both the initial stimulus for economic growth as well as the conditions for its long-term sustainability. Using cross-country time-series data for a sample of 89 countries for which long-term poverty incidence trends could be matched to growth and export performances, it is argued that countries with a high incidence of poverty have no option except a growth-cum-export strategy to reduce poverty. Redistributive policies to reduce poverty further are mainly a distinct option for countries that have already achieved a moderate level of poverty as well as higher per capita incomes. As Kaldor had emphasized as early as 1964, the lack of market access in industrial countries is an important contributing factor in hindering economic development and poverty reduction. Following Kaldor’s insights, this paper demonstrates that restricting market access prevents a large number of countries at the lowest ranks of the poverty ladder to escape extreme poverty.